Menyambut Era KUHP dan KUHAP Baru : Tantangan Perguruan Tinggi dalam Menyiapkan Generasi Penegak Hukum Baru - Iva Turisnur; Irfan Ardiansyah; Rustam (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This paper aims to identify and analyze the challenges faced by law schools in Indonesia in welcoming the new era of the Indonesian Criminal Code (KUHP) and the Code of Criminal Procedure (KUHAP). The research employs a descriptive qualitative methodology, utilizing library research techniques to gather data from relevant literature, books, documents, and journals. An introduction and data analysis were conducted to gain a deeper understanding of the issues discussed. The findings indicate that law schools face several key challenges, including the need to update the legal education curriculum to make it more applicable and relevant to modern societal needs. Additionally, enhancing faculty competencies through continuous training programs to teach new material is another significant challenge. Learning methods that emphasize practical experience, such as legal clinics and mock trials, are essential to help students apply legal theories in practice. Collaboration with law enforcement agencies is also a critical factor in preparing graduates who are not only technically competent but also ethical and understand the values of justice within the new legal framework. With collaboration among various stakeholders, legal education in Indonesia is expected to produce a new generation of skilled legal practitioners who can respond effectively to future legal challenges.